2021
DOI: 10.1126/science.abe5901
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of SARS-CoV-2 on mink farms between humans and mink and back to humans

Abstract: Animal experiments have shown that non-human primates, cats, ferrets, hamsters, rabbits and bats can be infected by SARS-CoV-2. In addition, SARS-CoV-2 RNA has been detected in felids, mink and dogs in the field. Here, we describe an in-depth investigation using whole genome sequencing of outbreaks on 16 mink farms and the humans living or working on these farms. We conclude that the virus was initially introduced from humans and has since evolved, most likely reflecting widespread circulation among mink in th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
1,170
4
21

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 1,019 publications
(1,297 citation statements)
references
References 54 publications
27
1,170
4
21
Order By: Relevance
“…Furthermore, SARS-CoV-2 RNA was present at low copy numbers in the intestinal tissue samples and rectal swabs of the vehicle source animals as well as their contacts but undetectable in the MK-4482/EIDD-2801-treated source group and co-housed contact animals. Phylogenetic analysis of outbreaks in mink farms revealed prolonged intra-colony circulation and zoonotic mink-to-human transmission 9 , leading us to select ferrets-members of the weasel genus closely related to minks-as a SARS-CoV-2 transmission model. We noted that the experimental infection of ferrets was strongly dependent on the amount of viral inoculum used.…”
Section: Nature Microbiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, SARS-CoV-2 RNA was present at low copy numbers in the intestinal tissue samples and rectal swabs of the vehicle source animals as well as their contacts but undetectable in the MK-4482/EIDD-2801-treated source group and co-housed contact animals. Phylogenetic analysis of outbreaks in mink farms revealed prolonged intra-colony circulation and zoonotic mink-to-human transmission 9 , leading us to select ferrets-members of the weasel genus closely related to minks-as a SARS-CoV-2 transmission model. We noted that the experimental infection of ferrets was strongly dependent on the amount of viral inoculum used.…”
Section: Nature Microbiologymentioning
confidence: 99%
“…Spill-back of SARS-CoV-2 to farmed minks, subsequent large-scale mink-to-mink transmission and, in some cases, zoonotic transmission back to humans revealed efficient viral spread among members of the weasel genus without previous adaptation [6][7][8][9] . Although mink farms reported elevated animal mortality and gastrointestinal and respiratory clinical signs 15 , outbreak follow-up revealed continued intra-colony spread for extended periods of time 9 , suggesting that the acute clinical signs in the majority of infected animals may be mild. These mink field reports corroborated results obtained with experimentally infected ferrets showing that mustelids of the weasel genus transmit SARS-CoV-2 efficiently without strong clinical disease manifestation 16,17 .…”
mentioning
confidence: 99%
“…Naturally acquired infections of SARS-CoV-2 have only been demonstrated in pet dogs and cats in domestic settings, in tigers (Panthera tigris), lions (Panthera leo) and a puma (Puma concolor) in zoological collections, and in farmed American mink (Neovison vison) [38,39,40,41]. All such cases of natural infection have been linked to initial transmission from humans to the animals in their care.…”
Section: Host Susceptibilitymentioning
confidence: 99%
“…Sequencing of viral genomes has shown that natural transmission has taken place amongst farmed mink following initial introductions by infected workers [38,39]. Transmission amongst separately housed mink suggests that the infection may have been spread by fomites, respiratory droplets or contaminated dust from bedding [39].…”
Section: Persistence and Spread In Wildlifementioning
confidence: 99%
See 1 more Smart Citation